KENDALA DALAM PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA: STUDI KUALITATIF: KENDALA DALAM PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA: STUDI KUALITATIF - Widjayanti, Yhenti; Ramadhan, Muhammad Putra; Aditya, Ronal Surya; Rahmatika, Qory Tifani; Sunaryo, Eri Yanuar Akhamad Budi; Evi, Nurul; Masfi, Ahmad; Afiani, Nurma (Jurnal Keperawatan Terapan, 2022)
Abstract: Breastfeeding is the best way to meet the nutritional needs for the growth and development of infants. Breastfeeding plays a role in cognitive, sensory, motor development and protection against infections and chronic diseases, but various obstacles are still found in the community. The study focused on the experience of ineffective breastfeeding among working mothers in Pucangsongo Village. Design of this study was Qualitative research with a phenomenological approach. Data was collected by interviewing five nurses and observing data in the field to obtain primary data and reviewing Pucangsongo Polindes documents to obtain secondary data. Triangulation of research data is done by triangulation of sources and methods. Data analysis through the stages of data reduction, data display, and drawing conclusions and notifications. Results of this study were obstacles faced by working mothers who experience problems with ineffective breastfeeding include the availability of advice and infrastructure for breastfeeding in the workplace. Failure to breastfeed for working mothers, namely busyness during work or company policies that are not cooperative in providing sufficient time for mothers to express breast milk. Health workers such as midwives also affect the experience of ineffective breastfeeding. Health workers have a very important role in protecting, promoting, and supporting breastfeeding businesses and must be seen in terms of their broad involvement in social aspects. Keywords: breastfeeding, experience, women’s employment